Peatland Organic Matter Chemistry Trends over a Global Latitudinal Gradient - Verbeke, Brittany Aiello (author)
A Thesis submitted to the Department of Earth, Ocean and Atmospheric Science in partial fulfillment of the requirements for the degree of Master of Science. === Spring Semester 2018. === April 16, 2018. === Decomposition, FTIR, Latitude, Organic Matter, Peatlands, Stability === Includes bibliographical references. === Jeffrey Chanton, Professor Directing Thesis; Robert Spencer, Committee Member; Olivia Mason, Committee Member.